Perfectionism and Burnout During the COVID-19 Crisis: A Two-Wave Cross-Lagged Study - Spagnoli, Paola; Buono, Carmela; Kovalchuk, Liliya Scafuri; Cordasco, Gennaro; Esposito, Anna (Frontiers in Psychology, 2021)
The current study aims at examining the relationship between the perfectionism two-factor model (i.e. concerns and strivings) and burnout’s dimensions measured through the BAT (Burnout Assessment Tool) through a longitudinal study. A two-waves cross-lagged study was conducted using path analysis in SEM (Structural Equation Modelling) on 191 workers. Results confirmed the predictive role of perfectionistic concerns on the burnout’s dimensions, whereas perfectionistic strivings were not significantly related, suggesting that perfectionism should be monitored by employers and clinicians in order to prevent employees’ burnout. Limitations and future research directions are envisaged.